Overview of development and challenges of attitude determination for rotary wing UAVs based on GNSS - Zeng, Yejia; Lu, Zukun; Xie, Yuchen; Ren, Binbin; Yu, Yi; Ni, Shaojie (Frontiers in Physics, 2025)
Attitude determination of rotary-wing unmanned aerial vehicles (RUAVs) is crucial for grasping their motion state and is a necessary condition to ensure the correct execution of flight missions. With the continuous development and the constant enhancement of measurement accuracy related to the Global Navigation Satellite System (GNSS), attitude determination based on GNSS have become the mainstream high-precision attitude measurement approach. This paper mainly discusses the relevant theories of using GNSS for RUAV’s attitude determination, and introduces the relevent key aspects that determine attitude accuracy in the attitude resolution process, such as integer ambiguity fixing, attitude solution algorithms, and integrated attitude measurement. It especially elaborates on the challenges that faced to be solved for current RUAVs to use the GNSS system for real-time and guarded attitude measurement.